Prognostic factors in the patients with T2N0M0 colorectal cancer. Issue 1 (December 2016) - Xu, Bin; Yu, Lin; Zhao, Li-Zhong; Ma, Dong-Wang
Abstract Background The 5-year survival rate of the patients with stage I colorectal cancer is about 90 %; therefore, adjuvant therapy has not been recommended after radical resection; however, about 16–26 % of T2N0M0 patients will be dead at 5 years despite radical curative resection. It indicated that there is a defined group of patients who are at high risk for relapse or metastasis despite radical operation. This study aimed to find the patients with T2N0M0 colorectal cancer at high risk for relapse or metastasis. Methods From January 1993 to December 2014, 812 patients with histologically confirmed stage T2N0M0 primary colorectal cancer treated by radical surgery with complete clinical follow-up data were eligible for this study. The medical records of all patients were collected and were retrospectively analyzed. Survival rates were calculated using Kaplan-Meier method, and survival cures were compared using the log-rank test. Cox proportional hazards model was used to analyze the significant factors defined in univariate test. Results The 5-year and 10-year overall survival rates were 81.9 and 67.7 %, respectively. Male gender, old age, lymphovascular permeation, perineural invasion, and poor differentiation were associated with low cancer-specific survival rates in Kaplan-Meier analysis. Multivariate analyses revealed old age, lymphovascular permeation, perineural invasion, and poor differentiation as significant independent factors predicting worse prognosis (P < 0.05). Conclusions Old age, lymphovascular permeation, perineural invasion, and poor differentiation are risk factors for the worse prognostic patients with T2N0M0 colorectal patients who would potential benefit from more aggressive therapy.